Business Succession Planning in Indian MSM-FOBEs: A Study Based on Managerial-Role Employees. (September 2014) - Jain, Sudhir Kumar; Jain, Nalin
Family owned business enterprises (FOBEs) are prolific contributors to the Indian economy. Micro, small and medium family owned business enterprises (MSM-FOBEs) form a substantial portion of Indian FOBEs. MSM-FOBEs are highly vulnerable to intergenerational business succession. The extent of succession planning, an important factor for the success of business succession, varies with the size of the MSM-FOBE. The number of managerial-role employees is one of the indicators of the size of the MSM-FOBE. The importance of business succession planning to the owner–manager is one of the determinants of the extent of succession planning in any MSM-FOBE. The importance of six succession planning issues to owner–managers is compared on the number of the managerial-role employees in their MSM-FOBEs. The study reveals higher importance of five succession issues to owner–managers of larger MSM-FOBEs that is, those with higher number of managerial-role employees. The lower importance of most succession planning issues among owner–managers of small Indian MSM-FOBEs (with no managerial-role employees) could be one of the reasons for their higher vulnerability to business succession.